Attitudes of Consumers from Educons University toward Advertising through Sport among the Question how often Consumers purchase Sporting Goods - Zoran Milosevic; Marina Vukotic; Dusan Stupar (Journal of Anthropology of Sport and Physical Education)
This research was aimed at gaining relevant knowledge about the attitudes of Educons University consumers toward advertising through sport among the question how often consumers purchase sporting goods. The sample included 200 students from Faculty of sport and tourism in Novi Sad, divided into six subsample groups: consumers who do not purchase sport goods at all, then consumers who purchase sport goods less than ones a month, next 1–3 a month, 4–6 a month, 7–9 a month, as well as consumers who purchase sport goods more than 10 times a month. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of (p=.000). Hence, it is interesting to highlight that it was found there were significant differences showed up between the consumers who purchase sport goods. The significant differences were found in two of three variables, while the consumers who purchase sport goods less than 3 times a moths had much more negative attitudes toward advertising though sport.